2022
DOI: 10.3389/fonc.2022.788968
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Data Correction Based PET/CT Radiomics Model for Predicting Lymph Node Metastasis in Clinical Stage T1 Lung Adenocarcinoma

Abstract: ObjectivesTo develop and validate the imbalanced data correction based PET/CT radiomics model for predicting lymph node metastasis (LNM) in clinical stage T1 lung adenocarcinoma (LUAD).MethodsA total of 183 patients (148/35 non-metastasis/LNM) with pathologically confirmed LUAD were retrospectively included. The cohorts were divided into training vs. validation cohort in a ratio of 7:3. A total of 487 radiomics features were extracted from PET and CT components separately for radiomics model construction. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Our results suggest that radiomics can predict the pathological remission of NSCLC after immunotherapy-based NAT. Similar to previous studies ( 19 , 47 49 ), the prediction efficiency of the entire model is higher than that of the single DL model and the radiomics traditional features combined clinical features model. CT images and clinicopathological information obtained before NAT were constructed as the before_rad_cil model.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results suggest that radiomics can predict the pathological remission of NSCLC after immunotherapy-based NAT. Similar to previous studies ( 19 , 47 49 ), the prediction efficiency of the entire model is higher than that of the single DL model and the radiomics traditional features combined clinical features model. CT images and clinicopathological information obtained before NAT were constructed as the before_rad_cil model.…”
Section: Discussionsupporting
confidence: 84%
“…The general procedure of radiomics is as follows: 1) Acquisition of medical imaging data; 2) Region of interest (ROI) segmentation and feature extraction; 3) Feature selection, model building, and validation; 4) Statistical data analysis. Since then, the concept of radiomics has been widely studied in the differentiation of benign and malignant lesions ( 18 ), in the preoperative prediction of lymph node metastasis in lung cancer ( 19 ), and in the assessment of the mutational status of genes such as Epidermal Growth Factor Receptor (EGFR) ( 20 ) and anaplastic lymphoma kinase (ALK) ( 21 ). More radiomics studies include the prediction of treatment effects and prognosis in cancer ( 22 , 23 ) and even in non-neoplastic diseases such as the early diagnosis of Alzheimer’s disease ( 24 ) and the rapid radiological diagnosis of coronavirus disease 2019 (COVID-19) pneumonia ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…employed LASSO logistic regression for feature selection combined with various oversampling techniques for imbalance correction to predict lymph node metastasis (LNM) in clinical stage T1 lung adenocarcinoma (LUAD). The authors reported highest performance increase of +0.05 AUC (0.70 AUC vs 0.75 AUC) utilizing the edited nearest neighbors (ENN) method ( 53 ). Du et al.…”
Section: Discussionmentioning
confidence: 99%
“…Since the accurate prediction of minority classes is crucial for clinical practice, re-sampling techniques that generate more minority examples, like Oversampling, have been shown to be effective in improving prediction accuracy [22]. However, only a limited number of studies have investigated the e cacy of re-sampling approaches on imbalanced PET radiomics [23,24]. In particular, Xie et al [24] conducted a multi-center study and highlighted the improvement of re-sampling techniques combined with classi ers on PET radiomicsbased prognostic performance.…”
Section: Introductionmentioning
confidence: 99%